Measurement of high-Q2 charged current deep inelastic scattering cross sections with a longitudinally polarised positron beam at HERA - Cooper-Sarkar, A; Devenish, R; Foster, B; Gwenlan, C; Walczak, R; Zeus Collaboration (Springer, 2010)
Measurements of the cross sections for charged current deep inelastic scattering in e+p collisions with a longitudinally polarised positron beam are presented. The measurements are based on a data sample with an integrated luminosity of 132 pb-1 collected with the ZEUS detector at HERA at a centre-of-mass energy of 318 GeV. The total cross section is presented at positive and negative values of the longitudinal polarisation of the positron beams. The single-differential cross-sections dσ/dQ2, dσ/dx and dσ/dy are presented for Q2>200 GeV2. The reduced cross-section σ̃ is presented in the kinematic range 200<q2<60000 0.006<x<0.562.="" a="" agree="" and="" are="" boson.<="" determine="" gev2="" hypothetical="" limit="" lower="" mass="" measurements="" model.="" of="" on="" p="" predictions="" results="" right-handed="" standard="" the="" to="" used="" w="" well="" with=""></q2<60000>